Genetic Polymorphism Cytochrome P4502a6 Allel *4 And *9: Studi On Glycohemoglobine Level Among Javanese Indonesian Smokers - Patramurti, Christine; Fenty, (Pharmaceutical Sciences and Research, 2019)
Nicotine, the active compound in cigarettes, was considered as the risk factor for type 2 diabetes mellitus (T2DM). In the human body, nicotine would be metabolized by the enzyme cytochrome P450 2A6 (CYP2A6). CYP2A6 was known to be highly polymorphic. The active form of this gene was CYP2A6 *1, while the CYP2A6 *4 and CYP2A *9 alleles were the inactive alleles. The presence of this inactive allele caused the decreased activity of CYP2A6 so that it would affect the level of nicotine in the blood and would eventually cause an increased blood sugar levels. This study aimed to determine the effect of CYP2A6 polymorphism on glycohemoglobine levels among Javanese smokers. The blood sugar levels were measured by hemoglobin A1c (HbA1c). In this study, 33 active smokers involved in the study were identified as slow metabolizers, by which 63.9% of all test participants had CYP2A6 *1/*4 genotype and as many as 6.1% of the test participants had the CYP2A6 *1/*4/*9. The HbA1c levels among the participants have been analyzed, 28 participants were in normal range (4.83-5.56%); 4 participants were identified in prediabetes condition (5.70% - 5.97%) and 1 participant was in diabetes with HbA1c level was 7.16%. This condition indicates that the presence of CYP2A6 *4 and *9 alleles will affect HbA1c levels which can eventually lead to T2DM disease.